THE IMPORTANCE OF MOTION GAMES IN LEARNING HANDBALL TACTICAL AND TECHNICAL ELEMENTS SPECIFIC TO VTH GRADE STUDENTS - Ileana Juravle (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This study mainly aims to determine the role that playing games have in learning and improvement of handball technical and tactical elements of fifth grade students that will be included in the school team. Motivational role of playing games is a decisive factor in terms of attracting children to practice handball. The emotional sphere of the training children's involvement in program or teacher's attitude towards them, or by the used methods in the preparation leads to success or failure of the activity itself. The study included 12 children who were included in the training program; they are showing interest and pleasure for the proposed activities. The results also confirm the proposed hypothesis and objectives of the study.